Pedagogia dos corpos: gênero e sexualidade em práticas curriculares de dois CMEI da cidade do Natal - RN - Oliveira Filho, João Batista de (2017)
This research has as locus two Centros Municipais de Educação Infantil (CMEI) in the Natal public educational system. Based on contributions from educational post-structuralism field realizing some mixings about gender, cultural and Foucault studies, it aims to discuss curricular practices related to gender and sexuality in classrooms with children that have 5 years old. It detaches as a research problem the way curricular practices produced by teachers work intelligibility as a cultural matrix that holds a “truth” of a named natural continuity between sex and gender, not allowing anything that disturbs this rule. With methodological base in some proceedings with ethnographical approach, that is observation and semi-structured interview, this study experienced classroom routine, gestures, movements, instruments use, orderings, teachers discuss and silences during their practices related to children gender and sexuality. In this empirical approaching, conceptual lens as: culture (VEIGA-NETO, 2003; PÉREZ GOMEZ, 1993; HALL, 1997), power relationships (FOUCAULT, 1984, 1989, 2014), curriculum (SILVA, 2010), gender (SCOTT, 1995; LOURO, 1997, 2008, 2015) and gender performativity (BUTLER, 2003), among others related to post-structuralism perspective that were tools to establish links to work with bodies pedagogy using curricular practices that supposed produce normality about gender and sexuality. In this sense, it points many convergences in the cultural, social and political fields that cross curricular field and teacher point of view, linking pedagogical relations connecting teachers and children. Analyzing this process, this research points conductive practices that support asymmetrical power relationships based on actions under actions, articulating productive exercises that privilege gender and sexuality forms in the binary and heteronormative way. Inserted in this instable dynamics are culture significances, pseudo naturals, to each one see his/her own body rule not only as something necessary but as natural, acting about his/herself, submitting or resisting power effects that act about their body in that context. In this sense, it is possible to affirm curricular practices in the CMEI present power strategies investing in the normative subjectivity of gender and sexuality.